2003
DOI: 10.1074/jbc.m208705200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Mitochondrial Permeability Transition by Creatine Kinase Substrates

Abstract: Mitochondria from transgenic mice, expressing enzymatically active mitochondrial creatine kinase in liver, were analyzed for opening of the permeability transition pore in the absence and presence of creatine kinase substrates but with no external adenine nucleotides added. In mitochondria from these transgenic mice, cyclosporin A-inhibited pore opening was delayed by creatine or cyclocreatine but not by ␤-guanidinopropionic acid. This observation correlated with the ability of these substrates to stimulate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
120
0
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(131 citation statements)
references
References 65 publications
2
120
0
5
Order By: Relevance
“…Furthermore, reduced neuronal damage and ROS formation were observed when cultures were administered with Cr at least 6 h before 3-hydroxyglutarate treatment (53). In isolated mitochondria, the inhibition of the MPT by CK substrates seems to be an important blocker of both necrotic and apoptotic cell death (42,52). Although Cr protected the brain against malonate-induced hydroxyl radical generation, due to increased high energy phosphate reserves (17), a direct involvement of Cr with cellular and mitochondrial ROS generation was not yet established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, reduced neuronal damage and ROS formation were observed when cultures were administered with Cr at least 6 h before 3-hydroxyglutarate treatment (53). In isolated mitochondria, the inhibition of the MPT by CK substrates seems to be an important blocker of both necrotic and apoptotic cell death (42,52). Although Cr protected the brain against malonate-induced hydroxyl radical generation, due to increased high energy phosphate reserves (17), a direct involvement of Cr with cellular and mitochondrial ROS generation was not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Cr is an excellent stimulant for mitochondrial respiration during PCr generation (31,40,41). Besides its role on energy metabolism it has recently been demonstrated that activation of mt-CK inhibits the mitochondrial permeability transition (MPT), a process that is involved in apoptosis (42). The postulated protective mechanism of mt-CK activity against MPT pore opening lies on functional coupling between the mt-CK reaction and oxidative phosphorylation (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These microcompartments control metabolite channeling between CK and ANT (Fig. 8), thus participating in the CK/phosphocreatine energy circuit (2) and possibly regulating mitochondrial permeability transition, one of the pathways leading to apoptosis (14,15,57). Under pathological conditions, these microcompartments can be disrupted, thus potentially leading to energy deficits and increased apoptosis (58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…ADP is subsequently reimported into the matrix space via ANT, an obligatory ATP/ADP antiporter, and phosphocreatine is released into the cytosol via mitochondrial porin (or voltagedependent anion channel, VDAC) in the outer mitochondrial membrane. This intimate exchange of substrates and products, the so-called functional coupling or metabolite channeling (10,11), fulfills important functions that may vary among different tissues, species, and developmental states (12,13): (i) phosphocreatine becomes the high energy intermediate that is exported from mitochondria into the cytosol (3); (ii) locally generated ADP stimulates oxidative phosphorylation (11); and (iii) ADP channeled through the MtCK/ANT interaction inhibits the Ca 2ϩ -induced opening of the mitochondrial permeability transition pore (14,15), a well known trigger of apoptosis (16,17). Thus, overexpression of uMtCK in many malignant cancers with especially poor prognosis (18,19) may be related to high energy turnover and failure to eliminate cancer cells via apoptosis.…”
mentioning
confidence: 99%